Valuta Asing: Peran dan Fungsinya dalam Sistem Pembayaran Internasional - Fadillah Fadillah; Adelliya Syahkilah; Aisyah Amrina Rosyada; Dwi Hasmidyani; Muhammad Akbar Budiman (Pusat Riset dan Inovasi Nasional, 2025)
Foreign exchange (forex) plays a crucial role in facilitating cross-border economic activities, particularly within the international payment system. Forex serves not only as a means of international payment but also as a medium of exchange and a tool for controlling currency exchange rates. Its presence enables smoother international transactions and supports macroeconomic stability. This study aims to examine the definition of forex in the context of the global economy, analyze its functions as a payment instrument, a medium of exchange, and an exchange rate control mechanism, as well as to discuss the fundamental differences between forex and local currency. These differences are reviewed in terms of their characteristics, usage, and impact on the national economy. The research uses a descriptive method with a literature study approach as the primary data source. The findings indicate that forex holds a strategic role in supporting international trade activities and serves as an essential instrument in monetary policy decision-making by financial authorities. Therefore, a thorough understanding of the role and function of forex is crucial for economic actors to effectively respond to global market dynamics and maintain national economic stability.